Tax Uncertainty as a Mediator in Audit Advice Dynamics - Porkas Sojuangon Lubis; Alistraja Dison Silalahi; Vince Ariany; Yenni Ramadhani Harahap; Heri Enjang Syahputra (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study investigates the effect of joint provision of audit and tax services on aggressive tax advice, with tax uncertainty assessment as a mediating variable. This research emphasizes individual professional judgment within integrated service structures a perspective that remains underexplored in current literature. Methodology/approach:A quantitative associative approach was employed, with data collected through questionnaires from 100 auditors and tax professionals working in Public Accounting Firms (KAP) in Medan. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. Findings:The results indicate that joint provision of audit and tax services significantly influences both tax uncertainty assessment and aggressive tax advice. Moreover, tax uncertainty assessment significantly affects aggressive tax advice and mediates the relationship between joint service provision and aggressive tax recommendations. Practical implications:These findings have practical implications for public accounting firm management to ensure effective cross-functional collaboration while maintaining professional standards and tax advice quality. Originality/value: This study extends the literature by introducing a behavioral perspective on tax professionals’ decision-making in joint audit–tax environments. By integrating ingroup–outgroup theory and tax uncertainty frameworks, it provides novel evidence from the Indonesian context, addressing a gap in existing research that has largely overlooked the psychological and organizational mechanisms shaping aggressive tax advice